2004
DOI: 10.1111/j.1365-2206.2004.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: Teenage pregnancy and motherhood: the contribution of support

Abstract: A B S T R AC TThis paper aims to provide a critical analysis of the role of support in teenage motherhood. Family, partner and peer support are considered and literature emanating from both the USA and UK is reviewed. In summary the research literature indicates that family support is particularly important to teenage mothers and has been found to have a positive influence on parenting behaviours and practices. However, the mother-daughter relationship is not always a straightforward one and conflict between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 19 publications
3
55
0
5
Order By: Relevance
“…In particular, no research has investigated social support for adolescent mothers in the neonatal nursery context. However, social support attenuates the effects of age on outcomes for adolescent mothers (Bunting and McAuley, 2004;Letourneau et al, 2004), suggesting supportive relationships may be important for adolescent mothers of preterm infants.…”
Section: Introductionmentioning
confidence: 92%
“…In particular, no research has investigated social support for adolescent mothers in the neonatal nursery context. However, social support attenuates the effects of age on outcomes for adolescent mothers (Bunting and McAuley, 2004;Letourneau et al, 2004), suggesting supportive relationships may be important for adolescent mothers of preterm infants.…”
Section: Introductionmentioning
confidence: 92%
“…Pregnant and parenting adolescents, in particular, need support to cope with stress, engage in quality interactions with their children, and take care of their child’s needs (Letourneau, Stewart, & Barnfather, 2004) and the literature reveals that support from the adolescent mother’s own mother and the father of her baby contribute to positive outcomes for these mothers and their babies (Bunting & McAuley, 2004). However, compared to non-pregnant adolescents, pregnant adolescents frequently receive less support from peers and their families and these low levels of support appear to be stable from prenatal to postpartum stages (Devereux et al, 2009).…”
Section: Risk and Protective Factorsmentioning
confidence: 99%
“…This research interviewed teens from low income areas and found that the pregnancy caused hardship for these young women. Both this study and the review by Bunting and McAuley (2004), however, only explored the teenage daughter -mother relationship. There was one study that partially explored mother daughter relationships but this was during the pregnancy only.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much of the literature that specifically considers women's relationship with their own mothers in the postnatal period is focused on adolescent mothers. For instance, a review of research in this area by Bunting and McAuley (2004) found that teenage mothers identified their mothers to be both a source of support and a source of conflict. The sources of conflict were not specifically identified in the studies reviewed, but it was suggested that these related to the teenagers' struggle for autonomy and independence, disagreements about living in the same household and taking responsibility for their baby.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation